Proyecto de producción y comercialización de una crema retardadora del vello corporal en el mercado Guayaquileño - Alcívar Millán, Viviana Elizabeth (2010)
The following grade Project is a resume of the main variables taken into account to the analysis of the female market of Guayaquil City and taking decisions supported by the interpretation of them for the introduction of a body hair growth retarder cream. It’s an intention to elaborate a product developed for reducing the frequency with which women resort to various methods to remove body hair, prolonging their effect and improving their results. Thus, to prolong the effects of waxing and other body hair elimination process the three major problems that are generated by those processes: the pain, time and money are attacked in a real way.